Westernization of the Ottoman Empire, Zionism and the Resistance of the Palestinian Society - Meirison Meirison (IAIN Ponorogo, 2020)
Abstract: Westernization due to backwardness in science and technology that was not taken care, because of their feeling of superiority over Europe. After underdevelopment in all areas, the Ottomans began reforms. However, the renewal focused on constitutions and parliaments that mimic the West, which fostered nationalism throughout the region. This facilitated Western intervention in the policies of the Ottoman government, which was very fragile and heavily in debt. Coupled with the defeat of the war with Russia and Western Europe. By conducting a historical discussion, the writer does a literature study and performs a comparative analysis of information and current events and develops them into a conclusion from the historical analysis obtained from various pieces of literature. Westernization is a gap opened by the West to change the Ottoman system of government in which Sultan Abdul Hamid II dissolved parliament. Westernization government after Sultan Abdul Hamid II had given support to Jews who favor Ottoman and Germans, but Jews only saw the opportunity to establish a Palestinian state with British support because basically, Ottoman Turkey which was motivated by Islamic Shari'at would be difficult to escape from the pressure of society Muslims and Arabs for the establishment of a Jewish state in Palestine. The Zionists had no choice but to support Britainالملخص: التغريب الذي أجراه ا العثمانيون بسبب التخلف في العلوم والتكنولوجيا التي لم يتم الاعتناء بها بسبب شعورهم بتفوق على أوروبا. وبعد التخلف في جميع المجالات، بدأ العثمانيون إجراء إصلاحات. ومع ذلك، ركز التجديد على الدساتير والبرلمانات التي تحاكي الغرب. وقد سهل هذا التدخل الغربي في سياسات الحكومة العثمانية التي كانت بالفعل هشة للغاية ومثقلة بالديون وأيضًا بسبب هزيمة الحرب مع روسيا وأوروبا الغربية. من خلال إجراء مناقشة بمنهج تاريخي ، يجري الكاتب دراسة على المصادر التاريخية في المكتبة والمتحف ثم أقوم بإجراء تحليل مقارن للمعلومات والأحداث الجارية ويطورها إلى استنتاج من التحليل التاريخي الذي تم الحصول عليه من مختلف المصادر. التغريب هو الفجوة التي فتحها الغرب لتغيير نظام الحكم المعثماني حيث تم حل البرلمان من قبل السلطان عبد الحميد الثاني. دعمت حكومة التغريب بعد السلطان عبد الحميد الثاني اليهود الذين كانوا في صالح الأتراك والألمان ، لكن اليهود لم يروا سوى فرصة لإقامة دولة فلسطينية بدعم بريطاني لأن الدولة العثمانية التي كانت تأسست على الشريعة الإسلامية سيكون من الصعب عليها الهروب من ضغوط المجتمع المسلمون والعرب لإقامة دولة يهودية في فلسطين. لم يكن أمام الصهاينة خيار سوى دعم بريطانيا Abstrak: Westernisasi dilakukan akibat keterbelakangan ilmu pengetahuan dan teknologi yang selama ini tidak dipedulikan akibat supremasi Turki Usmani di Eropa. Setelah ketinggalan dalam segala bidang terjadi Turki Usmani mulai melakukan pembaharuan. Akan tetapi pembaharuan terfokus kepada konstitusi dan parlemen yang meniru Barat yang menumbuhkan nasionalisme di seluruh wilayah. Hal memudahkan campur tangan Barat atas kebijakan pemerintahan Turki Usmani yang sudah sangat rapuh dan dililit hutang dan juga akibat kekalahan perang dengan Rusia dan Eropa Barat. Dengan melakukan pembahasan historis penulis melakukan studi pustaka dan melakukan analisa komparatif terhadap informasi dan kejadian yang ada sekarang dan mengembangkannya menjadi sebuah kesimpulan dari analisa sejarah yang didapatkan dari berbagai literatur. Westernisasi adalah celah yang dikuakkan oleh Barat untuk mengubah sistim pemerintahan Turki Usmani yang mana parlemen sempat dibubarkan oleh Sultan Abdul Hamid II. Pemerintahan westernisasi pasca Sultan Abdul Hamid II sempat memberikan dukungan kepada Yahudi yang berpihak kepada Turki Usmani dan Jerman akan tetapi Yahudi hanya melihat peluang mendirikan negara Palestina dengan dukungan Inggris karena pada dasarnya Turki Usmani yang dilatarbelakangi oleh Syariat Islam akan sulit melepaskan dari dari tekanan masyarakat Muslim dan Arab atas pendirian negara Yahudi di Palestina. Zionis tidak punya pilihan lain kecuali mendukung Inggris.